2016
DOI: 10.1111/cch.12383
|View full text |Cite
|
Sign up to set email alerts
|

Parents' voices: ‘why and how we advocate’. A meta‐synthesis of parents' experiences of advocating for their child with autism spectrum disorder

Abstract: Parenting a child with autism spectrum disorder (ASD) can be stressful, and accessing services can add to this stress. Self-efficacy, agency and advocacy are important for parents when accessing and using services. To develop insight into parental advocacy, a meta-synthesis was undertaken to consolidate the literature focussing on parents' experiences of advocating for their child with ASD. A qualitative meta-synthesis was conducted. Fifteen databases were systematically searched by using key terms related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 40 publications
5
69
0
1
Order By: Relevance
“…The selection process has been described in Boshoff et al (), with paired reviewers screening the titles, abstracts, and full texts of articles against the predetermined eligibility criteria, with discussion and full resolution of discrepancies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The selection process has been described in Boshoff et al (), with paired reviewers screening the titles, abstracts, and full texts of articles against the predetermined eligibility criteria, with discussion and full resolution of discrepancies.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported psychological outcomes for parents are primarily determined by individual coping responses, with action‐oriented strategies characterizing resilience (Whitehead, Dorstyn, & Ward, ). Parents describe advocacy as an important coping strategy that enables them to move forward by redirecting negative emotions into positive outcomes (Boshoff, Gibbs, Phillips, Wiles, & Porter, ; Dababnah & Parish, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A body of literature has explored parents' characteristics and experiences in terms of stress levels, quality of life, coping mechanisms and advocacy (2)(3)(4); however, the investigation of parents/caregivers' perspective on the effectiveness of treatments and services their children receive has been limited (5).…”
Section: Introductionmentioning
confidence: 99%
“…Parents (or other caregivers) are usually the most aware of the child’s development, health status, and current behaviors. Parents are often advocates and experienced reporters on the child’s health conditions (Boshoff et al 2016; DePape and Lindsay 2015). But, ASD interview instruments based on parent report also have potential shortcomings.…”
mentioning
confidence: 99%